A high-strength, high-thermal-conductivity PBO nano-insulating composite paper and its preparation method
By introducing mica sheets, chitosan and anhydrous sodium sulfate into the PBO fiber dispersion, a mica sheet/PBO nanocomposite acid gel was formed, and high-strength and high-thermal conductivity PBO nano-insulated composite paper was prepared through solvent exchange and hot pressing treatment, which solved the problems of poor interaction between PBO nanofibers and poor compatibility with inorganic fillers, and achieved excellent mechanical, thermal and insulation properties.
Patent Information
- Application Number
- CN202410871512.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-07-01
- Publication Date
- 2025-03-18
- Estimated Expiration
- 2044-07-01
AI Technical Summary
The existing PBO nanofibers have poor interactions and are not compatible with inorganic fillers such as mica sheets and montmorillonite, which limits their wider application in aerospace, electronic information and 5G communications.
By introducing mica sheets, chitosan and anhydrous sodium sulfate into the PBO fiber dispersion, a mica sheet/PBO nanocomposite acid gel was formed, and high-strength, high-thermal insulation composite paper was prepared by solvent exchange and hot pressing.
The mechanical properties, thermal conductivity and insulation properties of PBO nano-insulated composite paper were improved, with a tensile strength of 143.9~295.9MPa, a thermal conductivity of 2.8~4.3W/(m·K), a volume resistivity of 1.3~6.0Ω·cm, and an electric breakdown strength of 96~153kV/mm.
Smart Images

Figure CN118854722B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of nanofiber composite paper, and in particular to a high-strength and high-thermal-conductivity PBO nano-insulating composite paper and a preparation method thereof. Background Art
[0002] Traditional insulation paper has poor mechanical properties and poor thermal conductivity, which makes it difficult to meet the future development needs of electrical engineering. Poly(p-phenylene benzobisoxazole) (PBO) fiber has an outstanding thermal decomposition temperature (650°C), extremely high tensile strength (5.8GPa) and excellent flame retardant properties (limiting oxygen index of 68), and is known as a super fiber.
[0003] PBO nanofibers derived from PBO fibers have broad application prospects in aerospace, electronic information, and 5G communications. However, the interaction between PBO nanofibers is poor, and its compatibility with inorganic fillers such as mica sheets and montmorillonite is poor, which limits its wider application. At present, there are few reports on PBO nano-insulating composite paper. How to improve the interaction between PBO nanofibers and improve the stability of the nanofiber network is still a huge challenge. Summary of the invention
[0004] The purpose of the present invention is to provide a high-strength, high-thermal-conductivity PBO nano-insulating composite paper and a preparation method thereof, so as to solve the problems existing in the above-mentioned prior art.
[0005] To achieve the above object, the present invention provides the following solutions:
[0006] One of the technical solutions of the present invention is to provide a high-strength and high-thermal-conductivity PBO nano-insulating composite paper, wherein the raw materials include, by weight:
[0007] 80-100 parts of PBO fiber, 10-60 parts of mica flakes, 2-5 parts of chitosan, 4-8 parts of anhydrous sodium sulfate, 300-500 parts of methanesulfonic acid and 300-500 parts of trifluoroacetic acid.
[0008] The second technical solution of the present invention is to provide a method for preparing the above-mentioned high-strength and high-thermal-conductivity PBO nano-insulating composite paper, the steps comprising:
[0009] The PBO fiber is added into a mixed acid solution of methanesulfonic acid and trifluoroacetic acid, and stirred to obtain a PBO fiber dispersion solution;
[0010] Dispersing chitosan, mica flakes and anhydrous sodium sulfate in the PBO nanofiber dispersion, homogenizing and then standing to obtain a mica flake / PBO nanocomposite acid gel;
[0011] The mica sheet / PBO nanocomposite acid gel is immersed in water to perform solvent exchange to obtain a nanocomposite hydrogel;
[0012] The nanocomposite hydrogel is subjected to hot pressing to obtain the PBO nano-insulating composite paper.
[0013] Furthermore, the stirring is magnetic stirring, and the time is 48 to 96 hours, preferably 72 hours.
[0014] The purpose is to form a stable PBO nanofiber dispersion of PBO fibers in the mixed acid.
[0015] Furthermore, the homogenization speed is 10000-18000 rpm, and the time is 20-60 min, preferably, the speed is 15000-18000 rpm, and the time is 30-50 min.
[0016] Furthermore, the standing time is 10 to 30 hours, preferably 20 to 30 hours.
[0017] The mica flake / PBO nano-composite acid sol is obtained after homogenization, and the mica flake / PBO nano-composite acid sol is transformed into an acid gel after standing at room temperature.
[0018] Furthermore, the solvent exchange step is repeated at least once, preferably 6 to 10 times, and more preferably 8 to 10 times.
[0019] Preferably, the time for each solvent exchange is 2 h.
[0020] The solvent exchange process is to immerse the mica sheet / PBO nanocomposite acid gel in deionized water, during which the trifluoroacetic acid / methanesulfonic acid mixed acid and the deionized water undergo solvent exchange until the solution is neutral, thereby obtaining the mica sheet / PBO nanocomposite hydrogel.
[0021] Furthermore, the hot pressing pressure is 0.1-0.3 MPa, the temperature is 60-80°C, and the time is 15-30 h. Preferably, the pressure is 0.2-0.3 MPa, the temperature is 70-80°C, and the time is 20-30 h.
[0022] The present invention introduces mica flakes, chitosan and anhydrous sodium sulfate into the PBO nanofiber dispersion: the introduction of mica flakes hinders the migration of carriers in the structure and improves its insulation performance; the introduction of chitosan improves the interface compatibility between the PBO nanofiber and the mica flakes, reduces the agglomeration of the mica flakes, enhances its mechanical properties, and reduces the interface thermal barrier between the PBO nanofiber and the mica flakes, reduces the scattering of phonons, and improves its thermal conductivity; at the same time, the sulfate ions in the anhydrous sodium sulfate can absorb the hydrogen ions in the PBO nanofibers, further improve the π-π interaction between them, and promote the formation of gel. Thus, the mechanical properties, thermal conductivity and insulation properties of the PBO nano-insulated composite paper prepared by the present invention are improved.
[0023] The third technical solution of the present invention is to provide a method for improving the compatibility of PBO nanofibers and inorganic fillers in PBO nano-insulating composite paper, the steps comprising:
[0024] The PBO fiber is added into a mixed acid solution of methanesulfonic acid and trifluoroacetic acid, and stirred to obtain a PBO fiber dispersion solution;
[0025] Dispersing chitosan, mica flakes and anhydrous sodium sulfate in the PBO nanofiber dispersion, homogenizing and then standing to obtain a mica flake / PBO nanocomposite acid gel;
[0026] The mica sheet / PBO nanocomposite acid gel is immersed in water to perform solvent exchange to obtain a nanocomposite hydrogel;
[0027] The nanocomposite hydrogel is subjected to hot pressing to obtain the PBO nano-insulating composite paper.
[0028] Furthermore, the stirring is magnetic stirring, and the time is 48 to 96 hours, preferably 72 hours.
[0029] Furthermore, the homogenization speed is 10000-18000 rpm, and the time is 20-60 min, preferably, the speed is 15000-18000 rpm, and the time is 30-50 min.
[0030] Furthermore, the standing time is 10 to 30 hours, preferably 20 to 30 hours.
[0031] Furthermore, the solvent exchange step is repeated at least once, preferably 6 to 10 times, and more preferably 8 to 10 times.
[0032] Preferably, the time for each solvent exchange is 2 h.
[0033] Furthermore, the hot pressing pressure is 0.1-0.3 MPa, the temperature is 60-80°C, and the time is 15-30 h. Preferably, the pressure is 0.2-0.3 MPa, the temperature is 70-80°C, and the time is 20-30 h.
[0034] Furthermore, the mass ratio of the PBO fiber to the mica sheet is 8-10:1-6, preferably 9-10:1-4.
[0035] Furthermore, the mass ratio of the PBO fiber to chitosan is 80-100:2-5, preferably 90-100:3-5.
[0036] Furthermore, the mass ratio of the PBO fiber to anhydrous sodium sulfate is 20-25:1-2, preferably 90-100:5-8.
[0037] Furthermore, the mass ratio of methanesulfonic acid to trifluoroacetic acid in the mixed acid solution is 3-5:3-5.
[0038] Furthermore, the mass ratio of the PBO fiber to the mixed acid solution is 4-5:30-50, preferably, 9-10:80-100.
[0039] Technical solution 4 of the present invention: provides an application of the above-mentioned high-strength and high-thermal-conductivity PBO nano-insulating composite paper in electrical engineering.
[0040] The present invention discloses the following technical effects:
[0041] The present invention uses anhydrous sodium sulfate to modify PBO nanofibers, and sulfate ions can reduce the electrostatic repulsion between PBO nanofibers, improve the π-π interaction between PBO nanofibers, and promote their gelation. The introduction of mica sheets hinders the migration of carriers in the structure and improves its insulation performance; the introduction of chitosan improves the interface compatibility between PBO nanofibers and mica sheets, reduces the agglomeration of mica sheets, enhances its mechanical properties, and reduces the interface thermal barrier between PBO nanofibers and mica sheets, reduces the scattering of phonons, and improves its thermal conductivity. Based on this, the PBO nano-insulating composite paper prepared by the present invention has excellent mechanical properties, thermal conductivity and insulation properties. The example results show that the tensile strength of the PBO nano-insulating composite paper provided by the present invention is 143.9-295.9MPa, the thermal conductivity is 2.8-4.3W / (m·K), the volume resistivity is 1.3-6.0Ω·cm, and the electrical breakdown strength is 96-153kV / mm.
[0042] The present invention provides a method for preparing the above-mentioned high-strength and high-thermal-conductivity PBO nano-insulating composite paper. First, an appropriate amount of PBO fibers are placed in a methanesulfonic acid / trifluoroacetic acid mixed acid, and a PBO nano-fiber dispersion is obtained after magnetic stirring. Then, chitosan, mica flakes and anhydrous sodium sulfate are sequentially dispersed in the PBO nano-fiber dispersion, and a mica flake / PBO nano-composite acid sol is obtained by stirring with a high-speed homogenizer, and a mica flake / PBO nano-composite acid gel is obtained after standing at room temperature for a period of time. Finally, the mica flake / PBO nano-composite acid gel is immersed in deionized water for solvent exchange to obtain a nano-composite hydrogel, and the PBO nano-insulating composite paper is further obtained by hot pressing.
[0043] The preparation method provided by the present invention is simple to operate and suitable for industrial mass production, and the obtained high-strength and high-thermal-conductivity PBO nano-insulating composite paper is expected to be applied to some extreme electrical engineering environments. BRIEF DESCRIPTION OF THE DRAWINGS
[0044] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0045] Figure 1 The cross-sectional SEM images of the composite paper prepared in Comparative Example 2 and Example 1, wherein (a) is Comparative Example 2, and (b) is Example 1;
[0046] Figure 2 The stress-strain curves of the composite papers prepared in Examples 1 to 4 and Comparative Examples 1 to 2;
[0047] Figure 3 These are infrared thermal imaging photos of Comparative Example 2 and Example 1 heated to 65° C. and cooled for 10 s and 20 s, wherein (a) is Comparative Example 2 and (b) is Example 1;
[0048] Figure 4 It is a schematic diagram of gelation in a specific embodiment of the present invention. DETAILED DESCRIPTION
[0049] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as limiting the present invention, but should be understood as a more detailed description of certain aspects, features, and embodiments of the present invention.
[0050] It should be understood that the terms described in the present invention are only for describing a particular embodiment and are not intended to limit the present invention. In addition, for the numerical range in the present invention, it should be understood that each intermediate value between the upper and lower limits of the scope is also specifically disclosed. The intermediate value in any stated value or stated range, and each smaller range between any other stated value or intermediate value in the described range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.
[0051] Unless otherwise indicated, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art. Although the present invention describes only preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials associated with the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.
[0052] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments of the present invention description without departing from the scope or spirit of the present invention. Other embodiments derived from the present invention description will be apparent to those skilled in the art. The present invention description and examples are exemplary only.
[0053] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.
[0054] Unless otherwise specified, room temperature and normal temperature in the specific embodiments of the present invention refer to 20-30°C.
[0055] The present invention provides a high-strength and high-thermal-conductivity PBO nano-insulating composite paper, wherein the raw materials include, by weight:
[0056] 80-100 parts of PBO fiber, 10-60 parts of mica flakes, 2-5 parts of chitosan, 4-8 parts of anhydrous sodium sulfate, 300-500 parts of methanesulfonic acid and 300-500 parts of trifluoroacetic acid.
[0057] Preferably, the high-strength and high-thermal-conductivity PBO nano-insulating composite paper comprises, by weight, the following raw materials:
[0058] 90-100 parts of PBO fiber, 10-40 parts of mica flakes, 3-5 parts of chitosan, 5-8 parts of anhydrous sodium sulfate, 300-500 parts of methanesulfonic acid and 300-500 parts of trifluoroacetic acid.
[0059] More preferably, the high-strength and high-thermal-conductivity PBO nano-insulating composite paper comprises, by weight, the following raw materials:
[0060] 100 parts of PBO fibers, 40 parts of mica flakes, 3 parts of chitosan, 6 parts of anhydrous sodium sulfate, 300-500 parts of methanesulfonic acid and 300-500 parts of trifluoroacetic acid.
[0061] In the present invention, the length of the PBO fiber is preferably 10 to 20 cm, and can be purchased from commercial sources.
[0062] In the present invention, the mica flakes can be purchased from commercial sources, and the particle size is 10 to 20 microns. The mica flakes have excellent insulation properties, can hinder the migration of carriers in the structure, and improve the insulation properties of the PBO nano-insulation composite paper.
[0063] In the present invention, chitosan can be purchased from commercial sources, and the purity is preferably ≥95%. The introduction of chitosan improves the interface compatibility between PBO nanofibers and mica sheets, reduces the agglomeration of mica sheets, enhances their mechanical properties, and reduces the interface thermal barrier between PBO nanofibers and mica sheets, reduces the scattering of phonons, and improves their thermal conductivity.
[0064] In the present invention, anhydrous sodium sulfate can be purchased from commercial sources, and the purity is preferably ≥95%. Anhydrous sodium sulfate is used to modify PBO nanofibers. Sulfate ions can reduce the electrostatic repulsion between PBO nanofibers, increase the π-π interaction between PBO nanofibers, and promote their gelation.
[0065] In the present invention, the mass concentration of methanesulfonic acid is preferably ≥99%, and the mass concentration of trifluoroacetic acid is preferably ≥99%.
[0066] Figure 4 It is a schematic diagram of gelation in a specific embodiment of the present invention.
[0067] Example 1
[0068] The preparation steps of high-strength and high-thermal-conductivity PBO nano-insulating composite paper are as follows:
[0069] S1, 100 parts of PBO fibers were placed in 800 parts of a 1:1 methanesulfonic acid / trifluoroacetic acid mixed acid, and magnetically stirred for 72 hours to obtain a PBO nanofiber dispersion;
[0070] S2, then, 3 parts of chitosan, 40 parts of mica flakes and 6 parts of anhydrous sodium sulfate are dispersed in the PBO nanofiber dispersion in sequence to obtain a mixed solution;
[0071] S3, then, the mixed solution was stirred by a high-speed homogenizer (15000rpm, 30min) to obtain a mica flake / PBO nanocomposite acid sol, and the mica flake / PBO nanocomposite acid gel was obtained after standing at room temperature for 24 hours;
[0072] S4, then, immersing the mica sheet / PBO nanocomposite acid gel in deionized water for solvent exchange for 2 hours, the number of solvent exchanges is 8 times, and a nanocomposite hydrogel is obtained;
[0073] S5. Finally, hot pressing is performed at 0.2 MPa and 80° C. for 24 hours to obtain a high-strength and high-thermal-conductivity PBO nano-insulating composite paper.
[0074] Example 2
[0075] The preparation steps of high-strength and high-thermal-conductivity PBO nano-insulating composite paper are as follows:
[0076] S1, 90 parts of PBO fibers were placed in 1000 parts of a mixed acid of methanesulfonic acid / trifluoroacetic acid in a mass ratio of 1:1, and magnetically stirred for 96 hours to obtain a PBO nanofiber dispersion;
[0077] S2, then, 2 parts of chitosan, 10 parts of mica flakes and 8 parts of anhydrous sodium sulfate are dispersed in the PBO nanofiber dispersion in sequence to obtain a mixed solution;
[0078] S3, then, the mixed solution was stirred by a high-speed homogenizer (18000rpm, 20min) to obtain a mica flake / PBO nanocomposite acid sol, and the mica flake / PBO nanocomposite acid gel was obtained after standing at room temperature for 24 hours;
[0079] S4, then, immersing the mica sheet / PBO nanocomposite acid gel in deionized water for solvent exchange for 2 hours, the number of solvent exchanges is 6 times, and a nanocomposite hydrogel is obtained;
[0080] S5. Finally, hot pressing was performed at 0.1 MPa and 60° C. for 30 hours to obtain a high-strength and high-thermal-conductivity PBO nano-insulating composite paper.
[0081] Example 3
[0082] The preparation steps of high-strength and high-thermal-conductivity PBO nano-insulating composite paper are as follows:
[0083] S1, 80 parts of PBO fibers were placed in 600 parts of a 1:1 methanesulfonic acid / trifluoroacetic acid mixed acid, and magnetically stirred for 48 hours to obtain a PBO nanofiber dispersion;
[0084] S2, then, 5 parts of chitosan, 20 parts of mica flakes and 4 parts of anhydrous sodium sulfate are dispersed in the PBO nanofiber dispersion in sequence to obtain a mixed solution;
[0085] S3, then, the mixed solution was stirred by a high-speed homogenizer (13000rpm, 40min) to obtain a mica flake / PBO nanocomposite acid sol, and the mica flake / PBO nanocomposite acid gel was obtained after standing at room temperature for 20 hours;
[0086] S4, then, immersing the mica sheet / PBO nanocomposite acid gel in deionized water for solvent exchange for 2 hours, the number of solvent exchanges is 7 times, and a nanocomposite hydrogel is obtained;
[0087] S5. Finally, hot pressing was performed at 0.1 MPa and 70° C. for 15 hours to obtain a high-strength and high-thermal-conductivity PBO nano-insulating composite paper.
[0088] Example 4
[0089] The preparation steps of high-strength and high-thermal-conductivity PBO nano-insulating composite paper are as follows:
[0090] S1, 100 parts of PBO fibers were placed in 600 parts of a mixed acid of methanesulfonic acid / trifluoroacetic acid in a mass ratio of 1:1, and magnetically stirred for 72 hours to obtain a PBO nanofiber dispersion;
[0091] S2, then, 5 parts of chitosan, 60 parts of mica flakes and 8 parts of anhydrous sodium sulfate are dispersed in the PBO nanofiber dispersion in sequence to obtain a mixed solution;
[0092] S3, then, the mixed solution was stirred by a high-speed homogenizer (15000rpm, 50min) to obtain a mica flake / PBO nanocomposite acid sol, and the mica flake / PBO nanocomposite acid gel was obtained after standing at room temperature for 24 hours;
[0093] S4, then, immersing the mica sheet / PBO nanocomposite acid gel in deionized water for solvent exchange for 2 hours, the number of solvent exchanges is 8 times, and a nanocomposite hydrogel is obtained;
[0094] S5. Finally, hot pressing was performed at 0.1 MPa and 70°C for 30 hours to obtain a high-strength and high-thermal-conductivity PBO nano-insulating composite paper.
[0095] Comparative Example 1
[0096] Compared with Example 1, the difference is that anhydrous sodium sulfate and chitosan are not added, and the preparation steps are as follows:
[0097] S1, 100 parts of PBO fibers were placed in 800 parts of a 1:1 methanesulfonic acid / trifluoroacetic acid mixed acid, and magnetically stirred for 72 hours to obtain a PBO nanofiber dispersion;
[0098] S2, then, 40 parts of mica flakes were dispersed in the PBO nanofiber dispersion to obtain a mixed solution. Then, the mixed solution was stirred by a high-speed homogenizer (15000 rpm, 30 min) to obtain a mica flake / PBO nanocomposite acid sol, and the mica flake / PBO nanocomposite acid gel was obtained after standing at room temperature for 24 hours;
[0099] S3, then, immersing the mica sheet / PBO nanocomposite acid gel in deionized water for solvent exchange for 2 hours, the number of solvent exchanges is 8 times, and a nanocomposite hydrogel is obtained;
[0100] S4. Finally, hot pressing was performed at 0.2 MPa and 80° C. for 24 hours to obtain the PBO nano-insulating composite paper.
[0101] Comparative Example 2
[0102] Compared with Example 1, the difference is that chitosan is not added, and the preparation steps are as follows:
[0103] S1, 100 parts of PBO fibers were placed in 800 parts of a 1:1 methanesulfonic acid / trifluoroacetic acid mixed acid, and magnetically stirred for 72 hours to obtain a PBO nanofiber dispersion;
[0104] S2, then, 40 parts of mica flakes and 6 parts of anhydrous sodium sulfate were sequentially dispersed in the PBO nanofiber dispersion to obtain a mixed solution. Then, the mixed solution was stirred by a high-speed homogenizer (15000 rpm, 30 min) to obtain a mica flake / PBO nanocomposite acid sol, and the mica flake / PBO nanocomposite acid gel was obtained after standing at room temperature for 24 hours;
[0105] S3, then, immersing the mica sheet / PBO nanocomposite acid gel in deionized water for solvent exchange for 2 hours, the number of solvent exchanges is 8 times, and a nanocomposite hydrogel is obtained;
[0106] S4. Finally, hot pressing was performed at 0.2 MPa and 80° C. for 24 hours to obtain the PBO nano-insulating composite paper.
[0107] Test example
[0108] The performance of the high-strength and high-thermal-conductivity PBO nano-insulating composite papers prepared in Examples 1 to 4 and Comparative Examples 1 to 2 was tested. The test results are shown in Table 1.
[0109] The test method is as follows:
[0110] Tensile strength: According to ASTM D5568-08, the tensile properties of the samples were measured by a universal tensile testing machine;
[0111] Thermal conductivity test: The in-plane thermal conductivity of the sample was measured using the Hot Disk TPS2200 thermal constant analyzer from Swedish AB Company;
[0112] Volume resistivity: According to IEC 60243-1:2013, the volume resistivity of the sample is measured using a high resistance meter tester;
[0113] Breakdown strength: According to GB / T1408.1-2006, the breakdown strength of the samples was measured using an MPD-104 high voltage generator (Wuhan Patlab Technology Co., Ltd.).
[0114] Table 1
[0115]
[0116]
[0117] It can be seen from the performance data in Table 1 that the use of mica sheets and chitosan in the present invention can effectively improve the mechanical properties, thermal conductivity and insulation properties of PBO nano insulating paper. Among them, chitosan is crucial to the mechanical properties of PBO nano insulating paper. It can be seen from Comparative Examples 1 to 2 that PBO nano insulating paper without the addition of chitosan or anhydrous sodium sulfate has a lower tensile strength and is difficult to meet practical engineering applications. In addition, the PBO nano insulating paper of Example 1 has the best comprehensive performance, which is better than the currently commercially available insulating paper and has broad application prospects in extreme electrical engineering environments.
[0118] Figure 1 The cross-sectional SEM images of the composite paper prepared in Comparative Example 2 and Example 1, wherein (a) is Comparative Example 2, (b) is Example 1, and Figure 1 It can be seen that the cross section of Comparative Example 2 has more pores, indicating that the compatibility between its PBO nanofibers is poor, while the cross section of Example 1 presents a dense layered structure, and the PBO nanofibers and mica sheets in the cross section form a uniform multilayer structure. This is because a strong hydrogen bond is formed between the PBO nanofibers and the mica sheets, which improves the compatibility.
[0119] Figure 2 The stress-strain curves of the composite papers prepared in Examples 1 to 4 and Comparative Examples 1 to 2 show that Examples 1 to 3 have excellent tensile strength.
[0120] Figure 3 The infrared thermal imaging photos of Comparative Example 2 and Example 1 heated to 65°C and cooled for 10s and 20s, wherein (a) is Comparative Example 2, (b) is Example 1, and Figure 3 It can be seen that after Example 1 is heated to 65°C, its surface temperature quickly drops to 31°C after 20 seconds of cooling, which is higher than the surface temperature of Example 2 (38°C), indicating that Example 1 has a higher thermal conductivity and a better heat dissipation effect.
[0121] The embodiments described above are only descriptions of the preferred modes of the present invention, and are not intended to limit the scope of the present invention. Without departing from the design spirit of the present invention, various modifications and improvements made to the technical solutions of the present invention by ordinary technicians in this field should all fall within the protection scope determined by the claims of the present invention.
Claims
1. A high-strength, high-thermal-conductivity PBO nano-insulating composite paper, characterized in that: By mass, the raw materials include: 80-100 parts of PBO fiber, 10-60 parts of mica flakes, 2-5 parts of chitosan, 4-8 parts of anhydrous sodium sulfate, 300-500 parts of methanesulfonic acid and 300-500 parts of trifluoroacetic acid; The preparation steps of the high-strength and high-thermal-conductivity PBO nano-insulation composite paper include: adding PBO fibers into a mixed acid solution of methanesulfonic acid and trifluoroacetic acid, stirring to obtain a PBO fiber dispersion; dispersing chitosan, mica sheets and anhydrous sodium sulfate in the PBO fiber dispersion, homogenizing and then standing to obtain a mica sheet / PBO nano-composite acid gel; immersing the mica sheet / PBO nano-composite acid gel in water for solvent exchange to obtain a nano-composite hydrogel; and hot-pressing the nano-composite hydrogel to obtain the PBO nano-insulation composite paper.
2. A method for preparing the high-strength and high-thermal-conductivity PBO nano-insulating composite paper according to claim 1, characterized in that the steps include: The PBO fiber is added into a mixed acid solution of methanesulfonic acid and trifluoroacetic acid, and stirred to obtain a PBO fiber dispersion solution; Dispersing chitosan, mica flakes and anhydrous sodium sulfate in the PBO fiber dispersion, homogenizing and then standing to obtain a mica flake / PBO nanocomposite acid gel; The mica sheet / PBO nanocomposite acid gel is immersed in water to perform solvent exchange to obtain a nanocomposite hydrogel; The nanocomposite hydrogel is subjected to hot pressing to obtain the PBO nano-insulating composite paper.
3. The preparation method according to claim 2, characterized in that: The stirring is magnetic stirring, and the time is 48 to 96 hours.
4. The preparation method according to claim 2, characterized in that: The homogenization speed is 10000-18000 rpm, and the time is 20-60 min.
5. The preparation method according to claim 2, characterized in that: The standing time is 10 to 30 minutes.
6. The preparation method according to claim 2, characterized in that: The solvent exchange step is repeated at least once, and the time for each solvent exchange is 2 hours.
7. The preparation method according to claim 2, characterized in that: The hot pressing pressure is 0.1-0.3 MPa, the temperature is 60-80° C., and the time is 15-30 h.
8. Application of the high-strength and high-thermal-conductivity PBO nano-insulation composite paper as claimed in claim 1 in electrical engineering.
Citation Information
Patent Citations
Aramid mica nano composite material and industrial preparation method thereof
CN112647342A
High-strength PBO micro-nano composite paper and preparation method thereof
CN117364526A